Enhanced VOC detection capabilities of amorphous boron nanoparticles under visible light illumination - Sahin, Ayse Nur; Ozdemir, Zeynep Guven (ELSEVIER, 2026)
This study investigates the vapor sensing performance of amorphous boron particles toward acetone, ammonia, and isopropanol at room temperature under dark and visible light illumination. The highest sensor response was obtained for 500ppm acetone, under 485 nm light. The sensing behavior under 485 nm illumination was examined over acetone concentrations 250 and 750 ppm. Light exposure significantly enhanced sensor response and sensitivity, with the most pronounced improvement for acetone. This enhancement is attributed to photo-assisted charge carrier generation, where electron-hole pairs interact with surface-adsorbed oxygen species, accelerating surface reactions. Sensor performance was further assessed under synthetic air and different relative humidity levels, revealing stable and reproducible responses. Moreover, acetone's high dipole moment and dielectric constant facilitate stronger electrostatic interactions with the sensor surface, resulting in faster response and recovery. Overall, amorphous boron particles exhibit strong potential as low-cost, selective, and efficient VOC sensors operating under low-power light conditions.
Keywords: Amorphous boron particles; Visible light illumination; Sensing ability of VOCs; OPTICAL BAND-GAP; THIN-FILMS; SENSORS; NANOWIRES; Physics